Thermohydrodynamic analysis of high speed water-lubricated spiral groove thrust bearing considering effects of cavitation, inertia and turbulence. (March 2018) - Lin, Xiaohui; Jiang, Shuyun; Zhang, Chibin; Liu, Xiang
Abstract: A thermohydrodynamic cavitating flow lubrication model including effects of cavitation, inertia and turbulence for high speed water-lubricated spiral groove thrust bearing was established. The static characteristics of the water-lubricated spiral groove thrust bearing at high speed condition were investigated using this model. The numerical calculation results have shown that load carrying capacity and friction torque reduce due to inertia and cavitation in high speed condition, while that load carrying capacity and friction torque increase due to turbulence. The maximum temperature rise increases due to inertia effect, and reduces due to cavitation effect. In addition, the influence of inertia effect on the static characteristics of water-lubricated spiral groove thrust bearing was greater than the cavitation effect under high speed condition. Highlights: A thermohydrodynamic lubrication model of high speed water-lubricated spiral groove thrust bearing is developed. The effects of cavitation and inertia and turbulent are included in the model. The cavitation and inertia effects on static characteristics of water-lubricated spiral groove thrust bearing is discussed.